REVIEW AND ANALYSIS OF DATA PROCESSING INFORMATION TECHNOLOGIES IN THE COURSE OF MODERN COMPUTER SCIENCE - KRAVCHUK, OLHA; SYNYUK, NATALIA; KRAVCHUK, DENYS (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article focuses on the review and analysis of data processing information technologies in the course of modern computer science. The article also presents theoretical aspects of such concepts as algorithms, data structures, computer architecture, logic, software, programming languages and concepts of their development, which have a significant impact on technological progress and social development, which, in turn, contribute to innovations in various fields, from medicine to finance, making life easier and improving working conditions, creating new business sectors and labor markets that meet the requirements of the digital economy, changing the way people communicate, educate and interact in society, in particular through the development of social networks and Internet platforms. Information technology has become not only the basis of modern computer science, but also a key determinant of technological progress and societal development. Understanding their role and interconnection helps to unlock the potential of these industries for further development and achievement of new heights in technology and innovation. Informatics, as the science of information processing, and information technologies that provide tools for this processing, form the basis for modern programming. They provide not only the necessary knowledge and tools, but also define strategies and methodologies for software development. Computer science covers many aspects, such as algorithms, data structures, computing theory, and much more. However, at the first stages of study, the basics of computer science usually include concepts such as algorithms, data structure, logic, computer architecture, programming languages, and software. They provide not only the necessary knowledge and tools, but also define strategies and methodologies for software development. Computer science covers many aspects, such as algorithms, data structures, computing theory, and much more. However, at the first stages of study, the basics of computer science usually include concepts such as algorithms, data structure, logic, computer architecture, programming languages, and software , which are discussed in this article.